The smart non-profit : staying human-centered in an automated world - Kanter, Beth, 1957-; Fine, Allison H., 1964- (Ascent Audio, 2022)
A pragmatic framework for nonprofit digital transformation that embraces the human-centered nature of your organization In The Smart Nonprofit: Staying Human-Centered in an Automated World, a team of dedicated nonprofit thought leaders delivers a discussion of the information and tools nonprofit staffers and board members need to effectively use artificial intelligence without alienating the human stakeholders and donors on whom they rely. Each chapter of the book offers a narrative discussion of how AI affects a particular functional area in an organization that includes case studies and practical tips for the ethical use of AI. You'll discover explorations of: - The steps you need to take to become a smart nonprofit and how to effectively lead a digitally transformed organization - How to automate program delivery, fundraising, and the back office - Likely future developments in AI for nonprofit work, including a more diverse field of programmers and data scientists and data sovereignty Perfect for nonprofit leaders, board members, employees, managers, and founders, The Smart Nonprofit also belongs on the bookshelves of anyone interested in the intersection of leadership and technology.